2014
DOI: 10.1371/journal.pntd.0002955
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cell Response to Dengue Virus Infection in Human

Abstract: BackgroundDengue viral infection is a global health threat without vaccine or specific treatment. The clinical outcome varies from asymptomatic, mild dengue fever (DF) to severe dengue hemorrhagic fever (DHF). While adaptive immune responses were found to be detrimental in the dengue pathogenesis, the roles of earlier innate events remain largely uninvestigated. Invariant natural killer T (iNKT) cells represent innate-like T cells that could dictate subsequent adaptive response but their role in human dengue v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 67 publications
3
24
2
2
Order By: Relevance
“…This is in contrast to a previous study in children which showed that the frequency of iNKT cells in patients was similar to healthy donors [12]. Although the reasons for this difference in not clear, it is possible that the iNKT cell frequencies are different in adults and children.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This is in contrast to a previous study in children which showed that the frequency of iNKT cells in patients was similar to healthy donors [12]. Although the reasons for this difference in not clear, it is possible that the iNKT cell frequencies are different in adults and children.…”
Section: Discussioncontrasting
confidence: 99%
“…Although not significant, we observed that patients with DF had a higher frequency of iNKT cells and also higher iNKT cell numbers. In a previous study, it was shown that patients with DF produced more IFN-g than IL-4 when compared to those with DHF [12]. Therefore, iNKT cells could be playing a significant role in anti-viral defences against the DENV.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations